Program Pelatihan Kompetensi Pada Narapidana Narkoba Di Lembaga Pemasyarakatan Kelas IIA Banceuy Dalam Rangka Pengembangan Sumber Daya Manusia - Shinta Aryasopa (LPPAIK Universitas Muhammadiyah Bandung, 2021)
The training program is carrying out a process to change behavior or improve the abilities, skills, of a person and is implemented in a structured / systematic manner. The competency training program for prisoners is very necessary, with the aim that after leaving prison can easily live their lives, they can use the skills / abilities resulting from the training to be able to continue their life so as not to make the same mistakes, especially the status of ex-convicts often underestimated. by the community. The purpose of this research is to find out what kind of training program provided by the correctional institution to prisoners which aims to develop human resources. By using a qualitative descriptive research method approach, namely a study that describes and analyzes the phenomena or events that occur. The results of the study show that the training program for prisoners is very important in honing the competence of prisoners, many correctional institutions have facilitated this training program, but it is still considered not optimal with regard to the infrastructure that supports the implementation of the training, there are also other obstacles and roles. from other parties who are still lacking, this is very important to pay attention to because this training program can support the ability of prisoners who, after completing their criminal period, to re-enter with the community, can seek a better life. The author suggests that the facilities related to this training be improved, then it can provide an understanding to the surrounding community that prisoners are not trash and that they should be given assistance for their lives so that they do not make the same mistakes again.